2017
DOI: 10.5539/elt.v10n3p26
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Study for Secondary Stage EFL Textbook: EFL Teachers’ Perspectives

Abstract: This study aimed at evaluating EFL textbook for secondary stage in Saudi Public schools. Participants consisted of (100) male teachers and (73) female teachers teaching secondary stage students in two cities: Madinah and Dowadmi. The tool of the study designed to cover five dimensions: layout and design, the objectives of the textbook, teaching methods and activities, language skills, and evaluation. The results revealed that EFL textbook for Saudi secondary schools needs more development to be more effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Teaching materials develop teachers' professional knowledge and play a significant role in EFL teaching and learning. Thus, the careful selection of coursebooks and the appropriate and flexible use of them are important to reflect the aims, methods, and values of the teaching program (Al Harbi, 2017;Cunningsworth, 1995). This study clarified the use of coursebooks in EFL classrooms and reported that coursebooks should never be regarded as the only source to be followed page by page in every class.…”
Section: Discussionmentioning
confidence: 99%
“…Teaching materials develop teachers' professional knowledge and play a significant role in EFL teaching and learning. Thus, the careful selection of coursebooks and the appropriate and flexible use of them are important to reflect the aims, methods, and values of the teaching program (Al Harbi, 2017;Cunningsworth, 1995). This study clarified the use of coursebooks in EFL classrooms and reported that coursebooks should never be regarded as the only source to be followed page by page in every class.…”
Section: Discussionmentioning
confidence: 99%
“…As culture and language competence are closely connected, the ability to communicate needs the knowledge of thinking and acting properly in accordance with the language associated with the culture. Therefore, the idea of integrating language and culture became a topic to be discussed in the recent researches during the last ten years; especially at the issue of how culture is represented in the English textbook (Faris, 2014;Gunantar, 2017;Kim & Paek, 2015;Muhsen Al Harbi, 2017;Setyono & Widodo, 2019;Silvia, 2015). The integration of language teaching and culture brings a number of advantages (Crozet & Liddicoat, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Educational materials such as textbooks should be evaluated based on students' needs (Akbari & Pourabbas, 2015). Evaluating textbooks can reveal the connection between learning problems and the curriculum, and contribute to the incorporation of the objectives of the curriculum in the textbooks properly (Al Harbi, 2017). Evaluating educational resources and discovering the problems in the textbooks can also lead to the production of new books (The fundamental reform document of education, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental reform document of education (2011) also emphasizes that curricula and their content should be carefully reviewed to identify and correct irrelevant and inappropriate contents. Textbook research is essential as it is effective in designing appropriate learning opportunities for students (Al Harbi, 2017).…”
Section: Introductionmentioning
confidence: 99%